A novel field box girder welding robot and realization of all-position welding process based on visual servoing. (March 2021) - Guo, Jichang; Zhu, Zhiming; Sun, Bowen; Zhang, Tianyi
Highlights: A novel on-site all-position welding robot system for steel box girder is proposed, which can realize all-position automatic welding. A new visual sensor is proposed, which can realize several functions simultaneously based on single detection image. The welding forming control in field all-position welding of steel box girder can be realized successfully based on visual servo-control. Abstract: Box-type steel structure has been widely applied in the field of buildings and bridges because of its unique advantages. However, there are still many problems in field welding that need to be solved. In order to improve the level of automation and intellectualization in field welding of box girder, a new type of on-site all-position welding robot system is developed and designed in this paper. The convenience of on-site installation and debugging of the robot is realized by the scheme of permanent magnet adsorption and straight-arc combined track. The motion matching scheme of bilateral wheel-axle clamping makes the circumferential movement of the robot much smoother and more stable which makes the system with better overall force characteristics and load-carrying capacity. Then, a novel visual sensor based on combined laser structured lights is proposed and designed, which can realize several functions such as groove parameters detection, welding joint tracking and torch posture detection in field welding based on single detection image, so as to effectively improve the flexibility and intelligence of field welding robot. After that, based on the designed visual sensor and welding robot system, a visual servo-control system based on Visual Studio platform is established. Through the effective integration of detection image reading, image processing and calculation, image feature parameters transmission, motion control board call and feedback control signal output, the adjustment and control of welding torch's position and posture based on visual servo-control are realized. Furthermore, based on the kinematics calculation and the welding process requirements of the box girder, the welding process design is planned for the all-position welding of the box steel girder, which solved the technical problem of the rectangular fillet welding in the box steel butt welding (the welding torch position and posture transition control in right-angled corner of girth butt joint). Finally, all-position welding experiments of box steel girder were carried out. The results show that the welding robot based on visual servo-control can realize better control of weld formation in all-position welding of box steel girder.